2014
DOI: 10.1002/stem.1790
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cell Lines Isolated From Mouse Embryonic Stem Cells Exhibiting De Novo Methylation of the E-Cadherin Promoter

Abstract: Mouse embryonic stem cells (mESCs) and epiblast stem cells represent the na€ ıve and primed pluripotent states, respectively. These cells self-renew via distinct signaling pathways and can transition between the two states in the presence of appropriate growth factors. Manipulation of signaling pathways has therefore allowed the isolation of novel pluripotent cell types such as Fibroblast growth factor, Activin and BIO-derived stem cells and IESCs. However, the effect of cell seeding density on pluripotency re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These bindings increase cytoskeleton interaction with tight and gap junction proteins, thus increasing cell adhesion. Abundant literature shows that E-cadherin is involved in cell polarity [ 21 23 ], cell differentiation [ 24 , 25 ], and cell proliferation [ 26 ]. In the present study, we found that E-cadherin was significantly expressed in CAOMECS, at higher levels than normal healthy epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…These bindings increase cytoskeleton interaction with tight and gap junction proteins, thus increasing cell adhesion. Abundant literature shows that E-cadherin is involved in cell polarity [ 21 23 ], cell differentiation [ 24 , 25 ], and cell proliferation [ 26 ]. In the present study, we found that E-cadherin was significantly expressed in CAOMECS, at higher levels than normal healthy epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, human dermal fibroblasts (HDFs) have been shown to give rise to naïve human iPS cells when reprogrammed in the presence of LIF, FGF2 and TGFβ1 plus inhibitors of c-Jun NH2-terminal kinase, p38, MAPK and glycogen synthase kinase 3 (3i) [85] , thus demonstrating that the cell signalling context is critical to the determination of naïve and primed pluripotency rather than the two states representing a species difference. The derivation of various novel stem cell lines, including intermediate epiblast stem cells which exhibit dual responsiveness to LIF and ACTIVIN/NODAL signalling [86] , has challenged the concept of 2 distinct pluripotent states, instead suggesting that a spectrum of pluripotency exists, an idea we develop in Hawkins et al [87] . Thorough investigation into this spectrum of pluripotency, and therefore the transition from pluripotent cells to differentiated cells, should accelerate the delineation of mechanisms occurring throughout the reverse process, from a somatic cell to an iPS cell.…”
mentioning
confidence: 99%
“…We have previously shown that pluripotency is maintained in Ecad −/− mESCs and ENPS cells (mESCs exhibiting de novo methylation of the E-cadherin promoter) through the TGFβ signalling pathway 14 24 , specifically via Activin/Nodal, and that self-renewal is regulated via the FGFR1 pathway. However, mESCs treated with Epep or DECMA-1 did not induce Activin/Nodal-dependent pluripotency or FGFR1-dependent regulation of self-renewal despite ablation of STAT3 phosphorylation with both E-cadherin inhibitor treatments.…”
Section: Discussionmentioning
confidence: 99%
“… 19 have observed that disruption of E-cadherin mediated cell-cell contact does not influence many intracellular protein interactions with E-cadherin and concluded that most of these interactions are independent of cell-cell adhesion 19 . Therefore, it is possible that Epep and DECMA-1 inhibition of E-cadherin in mESCs does not disrupt cytoplasmic E-cadherin-protein interactions sufficiently for the switch to Activin/Nodal-dependent pluripotency and FGFR1-dependent self-renewal observed in Ecad−/− mESCs and ENPS cells 14 24 . Alternatively, this may reflect the activation of unknown signalling pathways capable of maintaining pluripotency and self-renewal in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation